Empowerment of Coastal Communities in the Utilization ofMangrove Non-Timber Forest Products: Pemberdayaan Masyarakat Pesisir dalam Pemanfaatan Hasil Hutan Bukan Kayu Mangrove - Dadang Mashur; Rusli, Zaili; Ikhsan, Masrul (Universitas Lancang Kuning, 2025)
Mangrove ecosystem has large natural resource potential and utilized improve welfare. However, utilization without equipped with good knowledge and environmental awareness will have an impact on damage to mangrove ecosystem. In general, use of mangrove wood is main choice for community, because it high economic value. Meanwhile, use of mangrove non-timber forest products (NTFPs) such as fruit and leaves is still rare. Aim service is to empower coastal communities to utilize mangrove NTFPs into products that have high economic value. The methods used are counseling, training, mentoring, field demonstrations, partnerships and campaigns or social movements carried out by the service team together with real work college students. The results of the service showed changes in behavior, increased knowledge, skills, attitudes, participation and environmental awareness of coastal communities regarding the use of mangrove NTFPs such as leaves made into waru sticks and jeruju sticks. Furthermore, community empowerment is carried out not only to improve community welfare, but also to support environmental sustainability.